Multiple Analyses of G-Protein Coupled Receptor (GPCR) Expression in the Development of Gefitinib-Resistance in Transforming Non-Small-Cell Lung Cancer - Kuzumaki, Naoko (Public Library of Science, 2012)
There is increasing evidence that functional crosstalk between GPCRs and EGFR contributes to the progression of colon, lung, breast, ovarian, prostate and head and neck tumors. In this study, we performed multiple analyses of GPCR expression in a gefitinib-resistant non-small cell lung cancer (NSCLC) cell line, H1975, which harbors an L858R/T790M mutation. To determine the expression profile of mRNAs encoding 384 GPCRs in normal human lung fibroblast (NHLF) and H1975 cells, a GPCR-specific microarray analysis was performed. A heat-map of the microarray revealed considerable differences in the expression of GPCRs between NHLF and H1975 cells. From the GPCR expression list, we selected some GPCR agonists/antagonist to investigate whether the respective ligands could affect the growth of H1975 cells. Among them, treatment with either a selective antagonist of adenosine A2a receptors, which were highly expressed in H1975 cell and another gefitinib-resistant NSCLC cells, HCC827GR cells or “small interfering RNA” (siRNA) targeting adenosine A2a receptors produced a significant decrease in cell viability of both H1975 and HCC827GR cells. Among up-regulated GPCRs in H1975 cells, Gs-, Gi- and Gq-coupled GPCRs were expressed almost equally. Among down-regulated GPCRs, Gi-coupled GPCRs were dominantly expressed in H1975 cells. The present results suggest that multilayered crosstalk between GPCRs and EGFR may play an important role in orchestrating downstream signaling molecules that are implicated in the development of gefitinib-resistant NSCLC.